Tradition meets technology: The role of Artificial Intelligence in Nahdlatul Ulama and Muhammadiyah’s digital adaptation - Nada-Qisthina, Dwi Sufa; Musyafak, Najahan (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2025)
The rapid development of Artificial Intelligence (AI) in the digital media landscape has generated a duality of concerns and hopes among religious organizations such as Nahdlatul Ulama (NU) and Muhammadiyah. On one hand, AI is perceived as potentially eroding humanistic values; on the other, it offers the promise of accelerating the dissemination of Islamic teachings through digital platforms. This study aims to examine the adaptation process of AI technology within the digital media ecosystems of both organizations and to identify the key enabling and inhibiting factors. Employing a descriptive qualitative approach, data were collected through in-depth interviews with selected informants and institutional document analysis. The study adopts Everett Rogers’ diffusion of innovation model, encompassing five stages: knowledge, persuasion, decision, implementation, and confirmation. Findings reveal that NU has adopted AI through platforms such as Siskader, Kitab AI, Pandai AI, and sentiment analysis, while Muhammadiyah has developed Chat HPT, Goal Align Assessment, and AI-based customer service tools. These adaptations are driven by pressures to modernize, the need for a progressive organizational image, cadre openness to innovation, and user enthusiasm. Conversely, limited financial resources, insufficient computational capacity, and prolonged training durations are significant barriers. The study underscores the importance of a collaborative approach that integrates Islamic values with digital innovation strategies to enhance the da’wah capacity and organizational transformation in the age of artificial intelligence. ***** Perkembangan pesat Kecerdasan Buatan (AI) dalam lanskap media digital telah menimbulkan dualitas kekhawatiran dan harapan di antara organisasi keagamaan seperti Nahdlatul Ulama (NU) dan Muhammadiyah. Di satu sisi, AI dipandang berpotensi mengikis nilai-nilai humanistik; di sisi lain, AI menawarkan janji untuk mempercepat penyebaran ajaran Islam melalui platform digital. Studi ini bertujuan untuk meneliti proses adaptasi teknologi AI dalam ekosistem media digital kedua organisasi tersebut dan untuk mengidentifikasi faktor-faktor pendukung dan penghambat utamanya. Dengan menggunakan pendekatan kualitatif deskriptif, data dikumpulkan melalui wawancara mendalam dengan informan terpilih dan analisis dokumen institusional. Studi ini mengadopsi model difusi inovasi Everett Rogers, yang mencakup lima tahap: pengetahuan, persuasi, keputusan, implementasi, dan konfirmasi. Temuan menunjukkan bahwa NU telah mengadopsi AI melalui platform seperti Siskader, Kitab AI, Pandai AI, dan analisis sentimen, sementara Muhammadiyah telah mengembangkan Chat HPT, Goal Align Assessment, dan alat layanan pelanggan berbasis AI. Adaptasi ini didorong oleh tekanan untuk modernisasi, kebutuhan akan citra organisasi yang progresif, keterbukaan kader terhadap inovasi, dan antusiasme pengguna. Sebaliknya, keterbatasan sumber daya keuangan, kapasitas komputasi yang tidak memadai, dan durasi pelatihan yang panjang merupakan hambatan yang signifikan. Studi ini menggarisbawahi pentingnya pendekatan kolaboratif yang mengintegrasikan nilai-nilai Islam dengan strategi inovasi digital untuk meningkatkan kapasitas da’wah dan transformasi organisasi di era kecerdasan buatan.